INFLUENCES OF SHADING AND FERTILIZATION ON ON-FARM YIELDS OF COCOA IN GHANA. (31st August 2016) - ASARE, RICHARD; ASARE, REBECCA ASHLEY; ASANTE, WINSTON ADAMS; MARKUSSEN, BO; RÆBILD, ANDERS
SUMMARY: Most cocoa farms in Ghana are cultivated in complex agroforest systems, with plant growth and cocoa productivity being affected. The objective of this study was to investigate how shade trees affect cocoa yield, temperature and soil nutrients in low-input cocoa systems. Establishing plots on 24 farms in four locations (districts) in Ghana, we assessed the influence of varying canopy cover and fertilization on cocoa yields. Results showed no relationship between canopy cover and cocoa yields in the light crop season (February to August). For the main crop season (September to January), there was an interaction between shade and yields: Yields were higher on no-shade plots than on shaded plots in two districts, whilst there were no differences at the two other districts possibly due to differences in precipitation and soil nutrient status. On the other hand, there was a positive effect of increased canopy cover on yields within the shaded plots. Soil nutrient analyses revealed no significant differences between shaded and no-shade plots and adequate levels of N, K +, Fe 2+, Cu 2+ and Zn 2+ were recorded. However, soil contents of P, C, Mg 2+ and Ca 2+ were below recommended values. Peak temperatures recorded in the cocoa canopies were above the recommended range for this species. Although shade trees had a slight modifying effect on peak temperatures, the magnitude appeared too small to have any practical effects.